2022
DOI: 10.3390/biomedicines10102659
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and Its Inflammatory Changes Linked to Various Systemic Diseases: A Review of Its Underlying Mechanisms

Abstract: Periodontitis is a chronic inflammatory disease of the gums. The incidence of periodontitis is increasing all over the world. In patients with periodontitis, there is gradual destruction of the periodontal ligament and the alveolar bone, and later, in advanced stages, there is tooth loss. Different microorganisms, the host’s immune response, and various environmental factors interact in the progression of this chronic inflammatory disease. In the present review, we discuss the epidemiology, clinical features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 113 publications
(158 reference statements)
0
31
0
1
Order By: Relevance
“…LPS bien conocido por su toxicidad y su capacidad de causar inflamación no deseada en el huésped, lo que le dio el nombre de endotoxina. La diferencia de estructura en LPS puede explicar los distintos mecanismos a través de los cuales las células huésped reconocen las especies bacterianas (45,56). Se considera un importante factor de virulencia de las bacterias gramnegativas y está formado por grandes moléculas de lípidos y polisacáridos (56).…”
Section: Lipopolisacáridos (Lps)unclassified
“…LPS bien conocido por su toxicidad y su capacidad de causar inflamación no deseada en el huésped, lo que le dio el nombre de endotoxina. La diferencia de estructura en LPS puede explicar los distintos mecanismos a través de los cuales las células huésped reconocen las especies bacterianas (45,56). Se considera un importante factor de virulencia de las bacterias gramnegativas y está formado por grandes moléculas de lípidos y polisacáridos (56).…”
Section: Lipopolisacáridos (Lps)unclassified
“…In addition, it has been reported that oral bacteria sometimes cause bacteremia by tooth extraction or periodontitis, affecting various systemic diseases, such as endocarditis, diabetes, arteriosclerosis, and so on. [8][9][10] Hence, ARB in the oral cavity may also be a cause of bacteremia. Therefore, we need to pay more attention to ARB in the oral cavity not only for infection control but also for prevention of systemic disease.…”
Section: Introductionmentioning
confidence: 99%
“…ARB in the oral cavity are considered to spread the infection to other sites in individuals and to others through conversing, coughing, and eating. In addition, it has been reported that oral bacteria sometimes cause bacteremia by tooth extraction or periodontitis, affecting various systemic diseases, such as endocarditis, diabetes, arteriosclerosis, and so on 8–10 . Hence, ARB in the oral cavity may also be a cause of bacteremia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Zhao and her colleagues excluded the group with systemic diseases, however they did not specify the methodology used to exclude systemic disease participants and did not perform detailed laboratory examinations on the individuals. It is well known that the range of systemic diseases is very broad (Bhuyan et al, 2022), and some of them have insidious clinical symptoms and are often overlooked by the patients themselves and their physicians. For example, the oral cavity and the intestine, two of the most complex microbial habitats in the body, are always interacting with each other.…”
mentioning
confidence: 99%